(untitled) (Bangladesh Journal of Neuroscience, 2026)
Rasmussens encephalitis is a chronic progressive neurological disorder of childhood. It is a rare inflammatory disease, characterized by intractable focal epilepsy, progressive hemiplegia, cognitive deterioration, unilateral inflammation of the cerebral cortex. Median age of onset is 6 year. Our case is a 7 year old boy presented in the department of Paediatric Neurology of BSMMU with the complaints of weakness of the right side of the body, focal onset seizure, cognitive declination and difficulty of speech. In addition to classical clinical presentation of Rasmussens encephalitis, MRI brain showed hemispheric atrophy of one cerebral hemisphere.